2015
DOI: 10.1038/npp.2015.75
|View full text |Cite
|
Sign up to set email alerts
|

Common and Dissociable Dysfunction of the Reward System in Bipolar and Unipolar Depression

Abstract: Unipolar and bipolar depressive episodes have a similar clinical presentation that suggests common dysfunction of the brain's reward system. Here, we evaluated the relationship of both dimensional depression severity and diagnostic category to reward system function in both bipolar and unipolar depression. In total, 89 adults were included, including 27 with bipolar depression, 25 with unipolar depression, and 37 healthy comparison subjects. Subjects completed both a monetary reward task and a resting-state ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(155 citation statements)
references
References 63 publications
4
150
1
Order By: Relevance
“…However, other studies in bipolar patients have shown a reduced reward responsiveness challenging the hypothesis of a general reward hypersensitivity model of bipolar disorder. Decreased striatal activations in response to reward stimuli were found in euthymic to mildly depressed (Trost et al, 2014), depressed bipolar patients (Redlich et al, 2015;Satterthwaite et al, 2015) and euthymic bipolar II/bipolar not otherwise specified patients (Yip et al, 2015); with the latter study reporting differential hypoactivations of both the dorsal and the ventral striatum during reward processing in bipolar disorder (Yip et al, 2015). These results are in line with the present findings of a reduced bottom-up responsivity of striatal regions (dorsal and ventral) in healthy MAD1L1 risk allele carriers.…”
Section: Discussionsupporting
confidence: 82%
“…However, other studies in bipolar patients have shown a reduced reward responsiveness challenging the hypothesis of a general reward hypersensitivity model of bipolar disorder. Decreased striatal activations in response to reward stimuli were found in euthymic to mildly depressed (Trost et al, 2014), depressed bipolar patients (Redlich et al, 2015;Satterthwaite et al, 2015) and euthymic bipolar II/bipolar not otherwise specified patients (Yip et al, 2015); with the latter study reporting differential hypoactivations of both the dorsal and the ventral striatum during reward processing in bipolar disorder (Yip et al, 2015). These results are in line with the present findings of a reduced bottom-up responsivity of striatal regions (dorsal and ventral) in healthy MAD1L1 risk allele carriers.…”
Section: Discussionsupporting
confidence: 82%
“…The reward neurocircuitry also appears to be affected by attachment, which may have implications for psychopathology later in life. For example, in depression the nucleus accumbens is less active which is largely responsible for the sense of anhedonia in depression (Satterthwaite et al, 2015). It is possible that the altered function of the nucleus accumbens developed in the early stages of life as a response to poor attachment increases the risk for anhedonia and depression.…”
Section: Neurocircuitrymentioning
confidence: 99%
“…Recently, several studies have explored the differences in FC between BD and MDD using resting-state (Ellard et al 2015; Goya-Maldonado et al 2016; Marchand et al 2013; Wang et al 2015) or task-related fMRI (Anand et al 2009; Redlich et al 2015; Satterthwaite et al 2015). We previously studies compared neuroimaging data between BD and MDD by constructing the functional network connectivity (FNC), composed of a whole brain graph with nodes defined by independent components analysis (ICA) (Jafri et al 2008).…”
Section: Introductionmentioning
confidence: 99%